Lithium-associated hypothyroidism and potential for reversibility after lithium discontinuation: Findings from the LiSIE retrospective cohort study. (March 2020) - Lieber, Ingrid; Ott, Michael; Öhlund, Louise; Lundqvist, Robert; Eliasson, Mats; Sandlund, Mikael; Werneke, Ursula
Background: The association between lithium and thyroid dysfunction has long been known. However, it remains unknown if lithium-associated hypothyroidism is reversible once lithium treatment has been stopped. Aims: To determine whether lithium-associated hypothyroidism was reversible in patients who subsequently discontinued lithium. Methods: A retrospective cohort study in the Swedish region of Norrbotten into the effects and side- effects of lithium treatment and other drugs for relapse prevention (Lithium – Study into Effects and Side Effects). For this particular study, we reviewed medical records between 1997 and 2015 of patients with lithium-associated hypothyroidism who had discontinued lithium. Results: Of 1340 patients screened, 90 were included. Of these, 27% had overt hypothyroidism at the start of thyroid replacement therapy. The mean delay from starting lithium to starting thyroid replacement therapy was 2.3 years (SD 4.7). In total, 50% of patients received thyroid replacement therapy within 10 months of starting lithium. Of 85 patients available for follow-up, 41% stopped thyroid replacement therapy after lithium discontinuation. Only six patients reinstated thyroid replacement therapy subsequently. Of these, only one had overt hypothyroidism. Conclusions: Lithium-associated hypothyroidism seems reversible in most patients once lithium has been discontinued. In such cases, thyroid replacement therapy discontinuation could be attempted much more often than currently done. Based on the limited evidence of our study, we can expect hypothyroidism to recur early after thyroid replacement therapy discontinuation, if at all.